O ensino de língua e a construção de princípios teórico-metodológicos à luz do Círculo de Bakhtin - Rodrigues, William Dahmer Silva (2024)
This work aims to propose theoretical-methodological principles, involved in the construction of stylistic-dialogical proposals, in light of the perspective of the Bakhtin Circle, for teaching mother tongue. From this perspective, the research architects theoretical-methodological principles for language teaching in a dialogic conception in the light of Bakhtin (2010, 2011, 2015, 2022) and Voloshinov (2017). It is based on an article written by Mikhail Bakhtin, in the 1990s. 1940, entitled Questions of stylistics in language teaching (2013), in which the author shares his experiences as a teacher at Escola Ferroviária nº 39 and Escola Básica nº 14. To achieve the proposition of principles, the following are defined as specific objectives: compose a theoretical construct about principles that govern Bakhtinian architecture, related to language teaching; delimit the concept of Bakhtinian stylistics, as well as its relationship with language teaching; investigate how the Bakhtinian notion of living language it manifests itself in the Brazilian context of mother tongue teaching. The methodology is classified as theoretical regarding its nature; regarding the approach, it is classified as qualitative; as for the objectives, it is exploratory; regarding procedures, it is bibliographical, since we seek to propose, in the end, methodological alternatives, which, in a dialectical relationship with the bibliographical work, constitute support for the proposition of the desired principles. The research presents, as a result, the formulation of four principles: All dialogue is unfinished and, therefore, must be analyzed based on its direction and incompleteness; every text is constituted from a thematic content, a style and a construction compositional; stylistic analysis in language teaching links the use of linguistic units to contextualized use and Every sign is ideological and reveals distinct echoes and voices. When placing the principles of the Circle, this work highlights, in its analysis, an architectural approach to language teaching, which underlies stylistic-dialogical work. With this perspective theoretical-methodological, the dialogical approach contributes to an approximation of the reality of living language, which gives a stylistic-dialogical look to any textual genre.